B06 Musculoskeletal injury and medical discharge prevalence during Army basic training - Martin, Henry; Rawcliffe, Alex; Roberts, Andrew (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Musculoskeletal injuries (MSKIs) pose the primary health and operational risk to the military trainee population particularly those within basic training, leading to several issues such as reduced training time, chronic morbidity, and inevitably increased medical discharge. The purpose of the study was to investigate the current incidence, prevalence, and nature of MSKIs across British Army basic training. In addition to identifying the prevalence of MSKI medical discharges concerning the type and nature of the injury. A retrospective analysis of the Army Recruiting and Initial Training Command MSKI and Medical Discharge database was undertaken. Injury data was collected from Primary Care Rehabilitation Facilities at British Army training units, using a standardised procedure. A multiple-choice questionnaire was used within the initial consultation with the clinician to determine the severity and progression of the injury, whilst consenting to a data privacy notice. Prevalence of MSKIs (% recruits) was articulated in relation to the total number of recruits starting each training year. Over the past decade MSKIs have declined from a peak of 47% in men and 58% in women in 2013/14, to 22% in men and 21% in women in the 2022/23 training year, with the prevalence of female MSKIs being lower than male counterparts for the first time in this population. Trauma and overuse injuries correspond for 48% and 52% of these MSKIs respectively in 2022/2023, whereas historically overuse injuries have been responsible for a greater proportion. These overuse and trauma injuries were most common in the early stages of training. Lower limb injuries were more prevalent throughout training, resembling 2021/22 data where lower limb injuries accounted for c.80% of total MSKIs among both sexes. The total number of MSKIs resulting in medical discharges was 70, constituting 1.1% of all recruits. Among these discharges, 54 were observed in men and 16 in women. The prevalence of MSKIs resulting in medical discharges was 4.5% in men and 12.4 % in women. The gap between MSKI prevalence between sexes has decreased with recent data showing prevalence being similar. Despite this, women had an increased risk of medical discharge, suggesting gender differences in the severity of MSKIs. To reduce MSKI prevalence, strategies should focus on lower limb injuries, with an emphasis on the early stages of training.